(3GdJMUjd aj eNJUQ GdJaUjd aj JaSjQ GdbQBf GdcQjes - (3GdegOhj , CMeO Hf YeGQ Hf CHj GdYHGS GdegOhj, CHh GdYHGS,J (B440 (3g` s
(3ChdgG (B:s
(3ShQI Gdcga Gdbhd ef ChdgG Edi bhdg JYGdi Ef GdPjf BefhG hYedhG GdUGdMGJ EfG dgG fVjY CLQ ef MSf YedG s
(3BNQgG (B:s
(3agPg GdCTjGA heG CTHggG jfHZi JLfH ESJYeGd Gdhba YdjgG hHYV Pdc CbHM ef HYV Je cJGH GdJMUjd ai eNJUQ GdJaUjd hJe HJeGeg LejY GdOjhGf s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B1 - (3U (B184 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B2 - (3U (B27s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG JdhjK s
(3eUOQ GbJfGA GdCUd (B:s
(3GdNRGfI GdYGeI HGdQHGW (B(89 (3b(B) s
Keywords: (3GdJaSjQ hYdhe GdbQBfs